Promoting Forest City Management Based On Islamic Approach - Mikhriani Mikhriani; Luthfi Maulana; Imam Nawawi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2019)
There are many Koranic verses revealed the structure of city space, including forest city itself. These verses confirmed the ancient history records that human being creates the great civilization. One of their prestigious creations is a modern management concept of structuring the forest city. It shows how to build a green space, an unpolluted air and water, and a healthy environment. This paper studied the Islamic approach to forest city management in light a concept of Maqasid al-Syariah of Abu Ishaq Asy-Syatibi. Maqasid al-Syariah are Islamic pillars whose goal that is keeping sustainability, the existence and continuity of human life. It means that Islam has serious concern over good environment and its impact on health and wellbeing. According to Islam, the destructive behaviors cause damage just toward a single part of the environment are as bad as those destruct all of it. Therefore, managing forest city as well as Koranic directions depicted within its verses is a duty of Muslim people and for both secular or Islamic government.